Positive deviance : Income inequality and entrepreneurs' pursuit of innovative entrepreneurship - Wei, Shihao; Wu, Zhan; Stenholm, Pekka; Su, Zhongfeng (Elsevier, 2026)
Drawing on anomie theory, this study examines the impact of income inequality on entrepreneurs' pursuit of innovative entrepreneurship and how this impact varies according to entrepreneurs' financial capital, government size, and governance quality. Utilizing a sample of 56,281 observations across 55 countries, this study finds that income inequality has a positive effect on entrepreneurs' pursuit of innovative entrepreneurship, and this effect is mitigated by government size and governance quality. Moreover, the positive effect of income inequality on innovative entrepreneurship is greater for entrepreneurs in the middle-income class than those in lower- and higher-income brackets. This study extends the implications of income inequality to innovative entrepreneurship and advances our knowledge of the boundary conditions of this relationship. Moreover, it contributes to the comparative international entrepreneurship literature by clarifying the crucial role of income inequality in explaining variations in innovative entrepreneurship across countries.